Upaya Mewujudkan Objektivitas dan Efektivitas dalam Penerapan Control Self Assessment - Rinjani Rinjani (E-Jurnal Akuntansi TSM, 2021)
This article aims to examine efforts to achieve objectivity and effectiveness in the implementation of Control Self Assessment (CSA). These efforts were reviewed through 4 elements which are prerequisites that organizations must have in implementing CSA, namely trust, open management style, sense of belonging of the organization, and culture of honesty, to find out how the implication of these elements relates to the implementation of CSA. The data and information used in this study come from books, articles, research journals, news and other literature sources that contain information on the application of CSA and other matters relevant to the title of this article. Based on the results of the study, it can be concluded that a culture of honesty is an absolute prerequisite and must be owned by every organization that wants to implement CSA effectively, because honesty is the basic behavior of objectivity, and objectivity is the most important aspect in determining the effectiveness of CSA implementation. This is also cannot be separated from the role of the internal auditor as a facilitator who always guides and supervises the assessment of risk and internal control carried out by management so that the implementation of CSA continues to run objectively.